Blockchain-Based Automated System for Identification and Storage of Networks. (20th February 2021) - Prashar, Deepak; Jha, Nishant; Shafiq, Muhammad; Ahmad, Nazir; Rashid, Mamoon; Amin Banday, Shoeib; Khan, Habib Ullah
Abstract : Network topology is one of the major factors in defining the behavior of a network. In the present scenario, the demand for network security has increased due to an increase in the possibility of attacks by malicious users. In this paper, a blockchain-based system is suggested for securely discovering and storing networks. Techniques such as cloud-based storage systems are not efficient and are lacking in trust, privacy, security, and data control. The blockchain-based technique suggested in this paper is capable of resolving these challenges. Experiments were performed using Mininet, Cisco Packet Tracer, and Ethereum blockchain with the network inference algorithm. This algorithm is capable of inferring the network topology even when only partial information regarding the network is available. The results obtained clearly show that the network is resistant to malicious users and various external attacks, making the network robust.